Experience report: Shared nursing management interfaces in the pediatric inpatient unit of a university hospital - Wilma Nunes Martins Zorzan; Natália Araujo de Almeida; Ana Caroline de Lara (Universidade de Pernambuco, 2021)
Objective: To report the experiences of nurses about the implementation of shared nursing management in a pediatric admission unit of a University Hospital. Method: Descriptive study, of the experience report type, which was based on the practices experienced by nurses of a pediatric hospital admission unit of a federal public teaching service, related to the implementation of a shared management model in the clinic, in order to guide the management actions of the unit promoting the development of professional autonomy and improving satisfaction with the work environment. Results: The process of implementing shared management was described, identifying the facilitating points and challenges faced during this process, as well as the results experienced during the year. Final considerations: Shared management requires the nurse to perform his managerial activities in a continuous and articulated way, sensitive and aware for the development of a work guided by the needs of the sector.